2014
DOI: 10.2217/pme.13.92
|View full text |Cite|
|
Sign up to set email alerts
|

Critical Appraisal of the Views of Healthcare Professionals with Respect to Pharmacogenomics and Personalized Medicine in Greece

Abstract: These findings provide the basis for assessing the views of healthcare professionals in relation to personalized medicine in Greece, and should help to facilitate the integration of genomics into the medical decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 23 publications
4
47
0
Order By: Relevance
“…3). These data are comparable to recent surveys in Greece [4,8] and the USA [2], indicating that more in-depth pharmacogenomics education should be implemented so that all practicing physicians feel more confident to exploit the benefits of pharmacogenomics in optimizing drug treatment modalities. From the above, it is evident that physicians should receive some basic pharmacogenomics education during their undergraduate and/or graduate training.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…3). These data are comparable to recent surveys in Greece [4,8] and the USA [2], indicating that more in-depth pharmacogenomics education should be implemented so that all practicing physicians feel more confident to exploit the benefits of pharmacogenomics in optimizing drug treatment modalities. From the above, it is evident that physicians should receive some basic pharmacogenomics education during their undergraduate and/or graduate training.…”
Section: Discussionsupporting
confidence: 82%
“…Also, the study sample of our survey was rather small compared to previous studies. However, one should also bear in mind that although this survey was a university-wide rather than a nation-wide survey, which included a smaller respondents sample, the resulting data were comparable to other previously conducted studies [2,4]. …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Such studies would facilitate adopting certain policies and performing the necessary steps that would expedite integration of genomics into healthcare. These studies, conducted in various countries in Europe and the US [3,4,5,6,7], have shown that the level of the general public's awareness of genomic medicine and its impact on society is often rather low, which constitutes a major barrier to expediting the implementation of genomic medicine. In addition, the lack of proper mapping of the opinions of various stakeholders leads to an inadequately regulated environment in the field.…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, argue that the bottleneck for the implementation of pharmacogenomics does not lie in the lack of evidence demonstrating clinical utility but rather lies in the unfamiliarity and lack of genetics knowledge among physicians and other health-care providers. [22][23][24] This bottleneck will be addressed within the U-PGx consortium through an e-learning tool, which aims to increase physician knowledge and know-how with pharmacogenomics.…”
mentioning
confidence: 99%